Cognitive Behavioral Therapy for Anxiety in Parkinsonʼs Disease: A Randomized Controlled Trial. Issue 11 (22nd February 2021) - Moonen, Anja J.H.; Mulders, Anne E.P.; Defebvre, Luc; Duits, Annelien; Flinois, Bérengère; Köhler, Sebastian; Kuijf, Mark L.; Leterme, Anne‐Claire; Servant, Dominique; de Vugt, Marjolein; Dujardin, Kathy; Leentjens, Albert F.G.
ABSTRACT: Background: Anxiety disorders are among the most prevalent and disabling neuropsychiatric syndromes in patients with Parkinsonʼs disease (PD), but no randomized controlled treatment trials of anxiety have been published to date. Objective: The aim of this study was to assess the effectiveness of cognitive behavioral therapy (CBT) in the treatment of anxiety in patients with PD. Methods: Forty‐eight patients with PD with anxiety were randomized 1:1 between CBT and clinical monitoring only (CMO). The CBT program was developed to specifically address anxiety symptoms in PD and consisted of 10 weekly sessions. Assessments were conducted by blinded assessors at baseline, at the end of the intervention, after 3 months, and after 6 months (CBT group only). Main outcome measures were the Hamilton Anxiety Rating Scale (HARS) and the Parkinson Anxiety Scale (PAS). Results: Both the CBT and CMO groups showed clinically relevant improvement. Although there was no between‐group difference in outcome on the Hamilton Anxiety Rating Scale (6.7‐point reduction in the CBT group versus 3.9‐point reduction in the CMO group; P = 0.15), there was both a statistically significant and a clinically relevant between‐group difference on the total PAS in favor of CBT (9.9‐point reduction in the CBT group versus 5.2‐point reduction in the CMO group; P = 0.012), which was due to improvement on the PAS subscales for episodic (situational) anxiety and avoidance behavior. This greater improvement was maintained at 3‐ and 6‐month follow‐ups. Conclusion: CBT is an effective treatment for anxiety in patients with PD and reduces situational and social anxiety, as well as avoidance behavior. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society